IMPROVING VOCABULARY MASTERY IN READING COMPREHENSION THROUGH WALL PICTURE - Mariana S.V, Vordesti; Wijaya, Bambang; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : This research is conducted in order to improve students’vocabulary in the easiest way through using wall picture at seventh grade of SMP Nusantara Indah Sintang. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. This research consisted of two cycles and each cycle consisted of four phases, they were:planning, action, observation and reflection. Each cycle was conducted in three meetings, so the researcher conducted this research in six meetings for one month and three weeks. To collect and analyze the data, the researcher used interview, observation, and the students’achievements in pre-test and post-test in order to support the data collected. The result of this research shows that the students’avarage score in pre-test was 45.76, the avarage score in post-test 1 was 65.76, and the avarage score in Post test 2 was 79.61, while based on the class percentage result from the pre-test to the post-tset 2 improve about 66.39%. From this result, the researcher concluded that using pictures at seventh grade of SMP Nusantara Indah Sintang can improve students’ vocabulary. Keywords :Vocabulary, Wall Picture Abstrak : penelitian ini dilakukan untuk meningkatkan kosa kata siswa dengan cara termudah melalui gambar dinding pada siswa kelas 7 SMP Nusantara Indah Sintang. Dalam melakukan penelitian ini, peneliti menggunakan Penelitian Tindakan Kelas sebagai metode. Penelitian ini terdiri atas dua siklus, setiap siklus terdiri atas empat tahap, yaitu: perencanaan, pelaksanaan, pengamatan, dan refleksi. Setiap siklus dilakukan dalam tiga pertemuan, jadi secara total peneliti melakukan penelitian dalam enam minggu selama satu bulan tiga minggu. Dalam mengumpulkan dan menganalisis data, peneliti menggunakan wawancara, pengamatan, dan pengujian pretest dan posttest nilai siswa. Hasil penelitian ini menunjukkan nilai rata – rata pretest siswa 45,76, nilai rata- rata posttest 1 65,76 dan nilai rata- rata posttest 2 79,61, sementara berdasarkan hasil persentase prestest menuju posttest 2 meningkat 66,39%. Dari hasil ini, peneliti menyimpulkan bahwa penggunaan gambar dinding pada siswa kelas tujuh SMP Nusantara Indah Sintang dapat meningkatkan kosakata siswa. Kata Kunci : Kosa kata, Gambar Dinding